Bioarchaeological evidence of one of the earliest Islamic burials in the Levant - Megha Srigyan; Héctor Bolívar; Irene Ureña; Jonathan Santana; Andrew Petersen; Eneko Iriarte; Emrah Kırdök; Nora Bergfeldt; Alice Mora; Mattias Jakobsson; Khaled Abdo; Frank Braemer; et al. (Communications Biology, 2022)
Ancient genomic and archaeological data combine to identify a surprisingly early Islamic burial in modern day Syria.